Increasing the Representation of Black Men in Medicine by Addressing Systems Factors. (25th October 2022) - Poll-Hunter, Norma I.; Brown, Zackary; Smith, André; Starks, Steven M.; Gregory-Bass, Rosalind; Robinson, Derek; Cullins, Maureen D.; Capers, Quinn; Landry, Alden; Bush, Antonio; Bellamy, Kimberly; Lubin-Johnson, Niva; et al.
Abstract : In 2015, data released by the Association of American Medical Colleges (AAMC) showed that there were more Black men applying and matriculating to medical school in 1978 than 2014. The representation of Black men in medicine is a troubling workforce issue that was identified by the National Academies of Sciences, Engineering, and Medicine as a national crisis. While premedical pathway programs have contributed to increased workforce diversity, alone they are insufficient to accelerate change. In response, the AAMC and the National Medical Association launched a new initiative in August 2020, the Action Collaborative for Black Men in Medicine, to address the systems factors that influence the trajectory to medicine for Black men. The authors provide a brief overview of the educational experiences of Black boys and men in the United States and, as members of the Action Collaborative, describe their early work. Using research, data, and collective lived experiences, the Action Collaborative members identified premedical and academic medicine systems factors that represented opportunities for change. The premedical factors include financing and funding, information access, pre-health advisors, the Medical College Admission Test, support systems, foundational academics, and alternative career paths. The academic medicine factors include early identification, medical school recruitment and admissions, and leadership accountability. The authors offer several points of intervention along the medical education continuum, starting as early as elementary school through medical school matriculation, for institutional leaders to address these factors as part of their diversity strategy. The authors also present the Action Collaborative's process for leveraging collective impact to build an equity-minded action agenda focused on Black men. They describe their initial focus on pre-health advising and leadership accountability and next steps to develop an action agenda. Collective impact and coalition building will facilitate active, broad engagement of partners across sectors to advance long-term systems change.